Arabic Language Practice in Islamic Boarding Schools : (a Linguistic Landscape Study) - Maf’udah, Syafiyatul; Bahruddin, Uril; Barry, Nur Hasan Abdul (Shaut al Arabiyyah, 2025)
The female Mambaus Sholihin Boarding School implements a bilingual policy, namely Arabic and English, in the daily life of the santri. This study aims to analyze the influence of the linguistic landscape (LL) on the practice of speaking Arabic in the pesantren. The linguistic landscape in this pesantren encompasses three main languages, namely Indonesian, Arabic, and English, with a specific focus on the role of Arabic in LL and its impact on the habit of speaking Arabic among the santri. A qualitative approach was used to collect data in the form of photographs of visual signs in the pesantren environment, both in the form of infrastructural information and regulative restrictions. The analysis was conducted based on the type of language used, the distribution of Arabic, and how the positional configuration of the sign supports the practice of Arabic. The results show that the dominant presence of Arabic signs in the pesantren landscape, both monolingual and bilingual, creates an adequate environment to motivate santri to speak Arabic. Arabic is often placed positionally higher, indicating its priority in pesantren culture. The alignment between the bilingual policy and the supportive linguistic landscape facilitates natural and contextualized language learning. This study provides implications that language use practices in pesantren can be integrated as teaching materials to support contextualized, meaningful learning of Arabic along with its integration into language teaching methods to strengthen students’ speaking competence.